Implementation Of The AHP Algorithm In The Performance Assessment Of Production Section Employees At PT XYZ - Uus Rusmawan; Enang Rusnandi (Politeknik Mardira Indonesia, 2024)
Employee performance assessment is an important element in human resource management, especially in the production sector, which affects the company's efficiency and productivity. PT XYZ, as a manufacturing company, requires appropriate methods to objectively assess employee performance. The Analytical Hierarchy Process (AHP) algorithm was chosen to overcome this problem, because of its ability to handle complex and multi-dimensional assessment criteria. This research aims to apply AHP in the production employee performance appraisal system at PT XYZ. The methods used include collecting performance data, mapping performance criteria and sub-criteria, as well as using AHP to calculate the weight and priority of these criteria. The output of this research is expected to be a more accurate system for assessing performance, which can be used by PT XYZ management for better decision making. Outcome targets include national scientific publications and development of an assessment system that can be applied directly